The emergence of environmental factors as catalysts for tourism demand: A case study on Romania - Eugenia Lucaşenco; Constantin-Marius Apostoaie; Alexandru Maxim (CES Working Papers, 2017)
The paper assesses the role of social, economic and especially environmental factors in determining general, as well as ecotourism demand in Romania. In order to provide in-depth insights, we utilize a two-step approach: cross-sectional analysis for 2013 and a fixed-effect panel analysis for the 2000-2013 timespan (employing a total of 22 explanatory variables). Each of these methods was applied considering the counties of Romania. The main results show that, over the last 15 years, social and economic factors have contributed to the evolution of tourism demand more than aspects related to the environment. However, the emerging trend observed in 2013 shows a significantly stronger impact of ecological determinants on both general, as well as ecotourism demand. In order to encourage the attractiveness of the tourism sector, local and regional authorities should channel their policies in a balanced manner towards all of the three components of an integrated and sustainable system.
Keywords: 330; cross-section analysis; ecotourism; environmental determinants; panel data analysis; Romania; sustainable tourism; tourism demand